(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article discusses the theoretical, methodological and substantive aspects of the genesis of the green economy in the paradigm of implementing the concept of sustainable development. The task of optimizing the management of natural resource potential predetermines the search for effective socio-ecological and economic solutions that differ significantly from historically established destructive practices of resource exploitation. As a result of the study, it can be argued that the green economy at the present historical stage claims to be a global development paradigm that meets the principles of sustainable functioning of socio-ecological-economic systems. The direction of the development vector of the green economy depends on the following factors: compliance of the models built with the principles of sustainable development and ensuring control over the effectiveness of the implementation of the stated principles.